2018
DOI: 10.1080/10428194.2018.1443337
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of ibrutinib and carfilzomib combination therapy for relapsed or relapsed and refractory multiple myeloma

Abstract: (2018) Phase 1 trial of ibrutinib and carfilzomib combination therapy for relapsed or relapsed and refractory multiple myeloma, Leukemia & Lymphoma, 59:11, 2588-2594, DOI: 10.1080/10428194.2018 ABSTRACTThis phase 1, dose-finding study investigated ibrutinib and carfilzomib ± dexamethasone in patients with relapsed or relapsed/refractory multiple myeloma (!2 lines of therapy including bortezomib and an immunomodulatory agent). Of 43 patients enrolled, 74% were refractory to bortezomib and 23% had high-risk cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 14 publications
6
25
0
Order By: Relevance
“…However, it should be noted that a higher dose of ibrutinib (840 mg once daily) was used in the current study compared with other haematological malignancies (420 mg or 560 mg once daily). The ibrutinib dose used in the current study was chosen based on clinical activity and a favourable safety profile observed at the 840 mg dose level of ibrutinib in combination with carfilzomib with or without dexamethasone and in combination with dexamethasone in two early phase studies in MM . Plasma exposures to ibrutinib and bortezomib were consistent with those previously reported, suggesting that drug‐drug interactions may not be contributing factors to the safety observations.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, it should be noted that a higher dose of ibrutinib (840 mg once daily) was used in the current study compared with other haematological malignancies (420 mg or 560 mg once daily). The ibrutinib dose used in the current study was chosen based on clinical activity and a favourable safety profile observed at the 840 mg dose level of ibrutinib in combination with carfilzomib with or without dexamethasone and in combination with dexamethasone in two early phase studies in MM . Plasma exposures to ibrutinib and bortezomib were consistent with those previously reported, suggesting that drug‐drug interactions may not be contributing factors to the safety observations.…”
Section: Discussionsupporting
confidence: 59%
“…This phase 2 study evaluated the efficacy and safety of ibrutinib in combination with bortezomib plus dexamethasone in patients with R/R MM who had received one to three previous lines of therapy. After 74 patients had received at least one dose of study treatment, study enrolment was suspended as a risk‐minimisation measure to address concerns over an increased incidence of serious and fatal infections compared with other studies of ibrutinib in R/R MM . While the incidence of infection of any grade in this study (80%) was similar to rates reported with ibrutinib in other haematological malignancies (68%‐78%) over median follow‐up durations of 9.4 to 33.4 months, the incidence of grade ≥3 infections (43%) was higher than rates previously reported with ibrutinib (7%‐29%) .…”
Section: Discussionmentioning
confidence: 62%
“…In osteoclasts or bone marrow stromal cells from patients with MM, ibrutinib downregulated the secretion of carcinogen-initiated chemokines and cytokines, including CCL3, TNFβ, APRIL, and CXCL12, blocked CXCL12induced adhesion and migration of MM cells and reduced IL6-induced cell growth [101]. In clinical trials, ibrutinib plus dexamethasone or ibrutinib-carfilzomib-dexamethasone demonstrated encouraging responses with a manageable safety profile [102,103].…”
Section: Btk Inhibitors In MMmentioning
confidence: 99%
“…Additionally, the treatment using ibrutinib in combination with carfilzomib ± dexamethasone was first evaluated in patients with relapsed or relapsed/refractory MM by Chari et al (2018) [75] in a phase 1 dose-finding trial. The outcomes demonstrated the combination therapy of ibrutinib (840 mg) and carfilzomib (36 mg/m 2 ) with dexamethasone showed the most promising result as it has the shortest median duration of response for patients who achieved above partial response which was 7.2 months.…”
Section: Ibrutinib For Multiple Myeloma (Mm)mentioning
confidence: 99%